2010
DOI: 10.1186/1710-1492-6-10
|View full text |Cite
|
Sign up to set email alerts
|

Rhinitis in the geriatric population

Abstract: The current geriatric population in the United States accounts for approximately 12% of the total population and is projected to reach nearly 20% (71.5 million people) by 2030[1]. With this expansion of the number of older adults, physicians will face the common complaint of rhinitis with increasing frequency. Nasal symptoms pose a significant burden on the health of older people and require attention to improve quality of life. Several mechanisms likely underlie the pathogenesis of rhinitis in these patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 110 publications
(163 reference statements)
1
48
1
3
Order By: Relevance
“…Cross-sectional and longitudinal studies have shown that rhinitis symptoms become milder with age (24)(25)(26). However, in this study, more than 40% of the elders with rhinitis presented moderate-severe disease.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Cross-sectional and longitudinal studies have shown that rhinitis symptoms become milder with age (24)(25)(26). However, in this study, more than 40% of the elders with rhinitis presented moderate-severe disease.…”
Section: Discussioncontrasting
confidence: 42%
“…This may be due to concomitant age-related changes in nasal physiology in the elderly (nasal glandular atrophy, vascular changes, decreased nasal humidification, decreased mucociliary clearance, and structural changes of the nose) (7,8,10,23), which may contribute to more frequent rhinorrhea. In fact, it is likely that several mechanisms underlie the pathogenesis of rhinitis in the elderly, with potential interaction between inflammatory conditions and the influence of aging on nasal physiology (24).…”
Section: Discussionmentioning
confidence: 99%
“…The 2005 National Center for Health Statistics Report noted the prevalence of AR as 10.7% in individuals aged 45-64 years, 7.8% in those 65-75 years old, and 5.4% in those older than 75 [40]. AR is an inflammatory disorder of the nasal mucosa characterized by nasal congestion, rhinorrhea, and itching, often accompanied by sneezing and conjunctival irritation.…”
Section: Ar In the Elderlymentioning
confidence: 99%
“…In fact, vasomotor rhinitis is the most common form of nonallergic rhinitis, particularly in elderly adults. 42 The present study has several limitations. First, a cross-sectional design was used; thus, causal or temporal relations could not be addressed.…”
Section: Discussionmentioning
confidence: 86%